A method of absorbed dose determination using vitamin B2 water for optical imaging of X-rays from high energy medical linear accelerators. (February 2020) - Toyonaga, Chihiro; Yamamoto, Seiichi; Yogo, Katsunori; Okudaira, Kuniyasu; Kawabata, Fumitaka; Nakaya, Takayoshi; Oguchi, Hiroshi
Abstract: Determination of absorbed dose distributions in phantoms in X-ray beams of high energy medical linear accelerators (LINAC) is important for quality control checks of the system. Although optical imaging of water during irradiations of X-ray beams from a LINAC is a promising method, depth dose profiles showed underestimation in deeper parts of the water mainly probably because of the angular dependency of Cerenkov-light produced in water. To solve the problem, the authors added vitamin B2 to water and obtained optical images with a high-sensitivity cooled charge coupled device (CCD) camera during X-ray beams irradiations. Then, the depth and lateral distributions of these optical images were evaluated and compared with those of the dose planning system. The depth dose profiles of vitamin B2 water were similar to those calculated by the dose planning system, although there was dependency on the vitamin B2 concentrations. The lateral profiles of the optical images of vitamin B2 water were slightly smoother than those of the dose planning system at the edge of the distribution. With the measured light spectra of the vitamin B2 water, it was confirmed that the Cerenkov-light was converted to longer wavelength of light by the addition of vitamin B2. The authors conclude that vitamin B2 water has a potential to be a promising material to reduce the difference from those of dose planning system for determining the depth dose profiles. Highlights: Vitamin B2 water is a promising material to obtain improved dose distributions of X-ray from LINAC using the optical method. The depth profiles of vitamin B2 water were improved and almost the same as those calculated by the planning system. Cerenkov-light was converted to longer wavelength of light by the addition of vitamin B2 to water.